Corporate Social Responsibility Based on Essential Awareness - La Ode Sumail, Rahman Pura (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study tries to investigate the relevance of the implementation of CSR based on the values of awareness related to governance, financial performance, and ihsan spirit. The manager of Islamic banks as respondents. They are given the freedom to determine opinions or opinions according to what they experience with a range of assessments 1-5. In order to get accurate information, trials, validity tests, reliability tests, data editing, data tabulation, linearity assumption tests, and data analysis through generalized structured component analysis (GSCA). Governance characterized by sharia concepts encourages awareness-based CSR implementation. If good governance, good financial performance, and strong spirituality, then awareness of implementing CSR is getting higher. Photographs of awareness of implementing CSR are not limited to accommodating the interests and needs of stakeholders as sounded by stakeholder theory and not merely explaining the behavior of boundaries and norms of society such as pulses theory, but behind the awareness of giving there is the power of giving that is a new spirit and the company is on the hill of victory. Indicators used are based on sharia concepts. CSR has intrinsic awareness not found in conventional companies and banks.